Human Affairs : Postdisciplinary Humanities & Social Sciences Quarterly (De Gruyter, 2007)
Postdisciplinary international journal for humanities and social sciences is published in English by the Slovak Academy of Sciences, Slovakia. The underlying editorial strategy is to advance human self-understanding and communication via publishing innovative theoretical, interpretative, critical and historical contributions transcending traditional disciplinary and cultural frontiers.